Is Taeniothrips inconsequens (Thysanoptera: Thripidae) a pest of stone and pip fruit trees in Argentina? - De Borbon, Carlos Manuel (2022)
The presence of the “pear thrips” Taeniothrips inconsequens has been cited in Argentina in 1921 by Teresa Joan. This has affected exports of fruit tree propagation materials. However currently there is a concern about that citation because it was probably an incorrect iden tification of the thrips species. The objective of this work was to confirm the presence of Taeniothrips inconsequens in fruit orchards in Argentina. Fruit orchards were sampled in the main producing areas of Argentina. A total of 10,696 specimens from 393 samples were examined and no T. inconsequens were found. The citation of this species for Argentina could be the result of misidentifications. Ninety percent of the collected specimens corresponded to four species of thrips: 37% Frankliniella australis, 29% Thrips tabaci, 14% Frankliniella occidentalis and 10% Frankliniella gemina. Of the remaining 10%, 2% were larvae and 8% corresponded to the species Aneristothrips rostratus, Frankliniella frumenti, Frankliniella schultzei, Frankliniella inesae, Frankliniella juancarlosi, Frankliniella spp, Leptothrips mali, Aeolothrips fasciatipennis, Arorathrips texanus, Tenothrips frici, Haplothrips spp, Haplothrips fiebrigi, Haplothrips trellesi, Thrips australis, Karnyothrips spp., and Caliothrips phaseoli.